The Effect of Principal's Transformational Leadership Style on Teacher Performance Mediated by Motivation and Job Satisfaction in Senior High Schools in Merangin District - Andriadi, Dian; Sulistyo, Urip; Sofyan, Sofyan; Habibi, Akhmad (Indonesian Educational Administration and Leadership Journal (IDEAL), 2026)
This study examines the influence of the principal's transformational leadership style on teacher performance in senior high schools in Merangin Regency with teacher work motivation and job satisfaction as intervening variables and tenure as moderating variable, using a quantitative explanatory survey approach and PLS-SEM analysis (SmartPLS 3.2.9) on a sample of 537 teachers (98.70% response). The results of the hypothesis testing indicate that transformational leadership has a significant positive effect on teacher job satisfaction (β=0.248; p=0.000), teacher work motivation (β=0.690; p=0.000), and teacher performance directly (β=0.282; p=0.000). Teacher work motivation has a very strong effect on teacher performance (β=0.502; p=0.000) and on teacher job satisfaction (β=0.656; p=0.000), while teacher job satisfaction has no significant effect on teacher performance (β=0.083; p=0.105). Teacher job satisfaction was not proven to be a mediator (β=0.021; p=0.117), nor was the mediation chain of motivation → satisfaction → performance (β=0.038; p=0.125). However, teacher work motivation became a strong partial mediator (indirect effect=0.346), so that the total effect of transformational leadership on teacher performance reached 0.628 (62.8%). Teacher tenure was not significant as a moderator. These findings confirm that transformational leadership improves teacher performance primarily through work motivation, so it is recommended to strengthen the dimensions of transformational leadership and strategies to increase teacher motivation for the Merangin Regency Education Office and MKKS to improve the quality of learning.